Association between markers of left atrial cardiopathy and cognitive decline in the absence of atrial fibrillation. (20th December 2022) - Li, Zhe; Marion, Danielle; Blair, Jessica; Soliman, Elsayed Z.; Gladstone, David J.; Kamel, Hooman; Manuel, Doug; Edwards, Jodi D.
Abstract: Background: Whether atrial cardiopathy is independently associated with cognitive impairment in the absence of atrial fibrillation (AF) remains unknown. This longitudinal cohort study aims to investigate associations between markers of left atrial cardiopathy and cognitive decline, and to identify longitudinal trajectories of cognitive decline in aging adults without AF over time. Method: A cohort of adults ≥45 years of age with no prior AF or cognitive impairment (N=21, 869) was ascertained from the REGARDS (Reasons for Geographic and Racial Differences in stroke) prospective cohort study database. Markers of left atrial cardiopathy included atrial premature complexes (APCs) and N‐Terminal pro‐Brain Natriuretic Peptide (NTpro‐BNP). Cognitive status was measured using Six‐Item Screener (SIS) and an SIS score <5 was defined as cognitive impairment. Cox proportional hazards regression was used to estimate the cause‐specific hazard for primary (cognitive impairment) and secondary outcomes (stroke). Cognitive status trajectories were identified using latent class growth models. Baseline characteristics associated with each trajectory were identified using multinomial logistic regression. Result: During a mean follow‐up of 9.9 years, 6, 060 participants had incident cognitive impairment and 876 had a stroke. APCs increased the hazard of cognitive impairment by 10% (hazard ratio [HR], 1.10, 95%CI: 1.00‐1.20) and stroke by 9% (HR, 1.09, 95%CI: 1.01‐1.18). Elevated NTpro‐BNP increased the hazard of cognitive impairment by 55% (HR, 1.55, 95%CI: 1.17‐2.04) and stroke by 35% (HR, 1.35, 95%CI: 1.13‐1.60). Three unique cognitive trajectories were identified: while 85% showed a normal and stable trajectory of SIS scores, 13% showed a progressively decreasing trajectory, and 2% showed a dramatic decrease in SIS scores. Age, coronary artery disease, diabetes, and NTpro‐BNP were all associated with worse cognitive trajectories. Conclusion: We showed that markers of left atrial cardiopathy including APCs and elevated NTpro‐BNP were associated with an increased risk of cognitive impairment and stroke in the absence of AF. Adults with these markers followed three unique longitudinal cognitive trajectories. These findings indicate that markers of left atrial cardiopathy (APCs and NTpro‐BNP) may have significant implications for early diagnosis and prevention of cognitive impairment.